A book club to die for - St. James, Dorothy (St. James, Dorothy. Beloved bookroom mysteries, 2023)
"When a member of an exclusive book club is checked out, spunky librarian Trudell Beckett must sort fact from fiction to solve the murder. The Cypress Arete Society is the town's oldest and most exclusive clubs. When assistant librarian Trudell Beckett is invited to speak to the group about the library, its modernization, and her efforts to bring printed books to the reading public, her friend Flossie tags along. Flossie has been on the book club's waiting list for five years, and she's determined to find out why she's never received an invitation to join. But not long after Tru and Flossie arrive for the meeting, they're shocked to find the club's president, Rebecca White, dead in the kitchen. Rebecca was a former TV actress and local celebrity but was not known for being patient or pleasant. She'd been particularly unkind to the book club's host for the evening, who also happens to be the mother of Detective Jace Bailey, Tru's boyfriend. And Rebecca had made it clear that she didn't think Flossie was book club material. With Tru's boyfriend and one of her best friends wrapped up in a murder, she has to work fast to figure out who cut Rebecca's story short before the killer takes another victim out of circulation ..."-- Back cover.